System modelling and controller design of active thermosiphon beam - Zuo, Zhenye (2019)
HVAC system is very important to the building systems not only because they provide thermal comfort and maintain fresh air, but also because that it takes up to 50% of the building energy consumption, especially in tropical countries like ASEAN. Active thermosiphon beam (ATB) as a new technology, once adopted, will decrease the HVAC system energy consumption in an obvious way when compared to the traditional air-conditioning and VAV systems. So, the performance and detailed controlling research regarding active thermosiphon beam is very meaningful to the society. This thesis has described the principles of ATB operation, and based on the actual ATB working environment in NTU campus lab, system modelling had been made to create a mathematic model for the ATB cooling and ventilating system. Then a series of performance and response test had been carried out to verify the actual system modelling. After the modelling process, the controlling test had been carried out separately on temperature and ventilation process. And based on the test, the controlling parameters for the PID controllers could be defined and used in the simulation process. The simulation results had been shown in graphs and the response and performance of the designed controller had been discussed. Future developing directions have also been mentioned at the end of the thesis.